Preparation of biodegradable membrane utilizing chitosan and polyvinyl alcohol, and assessment of its performance after coating with graphene conductive ink - Meshram, Sumit Maya Moreshwar; Gonugunta, Prasad; Taheri, Peyman; Jourdin, Ludovic; Pande, Saket (Frontiers in Membrane Science and Technology, 2025)
Biodegradable membranes are crucial for environmental applications, offering sustainable and low-impact solutions. These membranes play a vital role in biodegradable batteries by separating the anode and cathode while facilitating proton movement. The aim of this study is to develop a biodegradable membrane using biodegradable polymers such as chitosan (CS) and polyvinyl alcohol (PVA), reinforced with filter paper. In this research, a cost effective, biodegradable membranes using CS, PVA, and a 1:1 CS/PVA composite through solution-casting method were synthesized. The membranes were reinforced with cellulose filter paper and coated with water-resistant graphene conductive ink. Performance metrics, including swelling ratios, water uptake, ion exchange capacity, oxygen diffusion, proton conductivity, and degradation in compost tea, were evaluated. Uncoated CS membrane exhibited the highest water uptake (94.10%), while uncoated PVA membrane demonstrated the highest swelling ratio (150%) and ion exchange capacity (3.94 meq/g). Coated CS/PVA membrane showed the lowest oxygen diffusion coefficient (0.058 × 10−5 cm2/s) and the highest proton conductivity (1.74 mS/cm). All membranes exhibited slow degradation over 100 days. The findings of this research have significant implications beyond the laboratory, presenting a biodegradable, cost-effective, and environmentally sustainable alternative to conventional membranes. These membranes can be utilized in the construction of biobatteries, which, in turn, can be employed to power low-cost devices.